CULTURAL LITERACY ANALYSIS OF PGSD STUDENTS IN TANAH AIR NUSANTARA STUDENT EXCHANGE PROGRAM - Hana Sakura Putu Arga; Siti Ruqoyyah; Medita Ayu Wulandari (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to determine PGSD students' cultural literacy abilities to adapt to the diversity of the nation, including how to behave, how to communicate, and how to interact between one and another through an Indonesian student exchange program. In this program students from several universities were united in an online learning process and it was hoped that through this program every student had the ability to understand various ethnic groups, languages, beliefs, habits, customs, and social strata as a national identity. This study utilized a descriptive method with the research subjects of PGSD students in "PERMATA" program from several universities in Indonesia. The instruments used in this study were open questionnaires, interviews, documents, and field notes. Research result revealed that online learning conducted on PGSD students in “PERMATA” program provided a positive impact on students’ cultural literacy. Students could easily adapt to various differences that exist in accordance with their respective cultural conventions. This could be seen from the beginning of the meeting, in which students were able to communicate well and to respect others by speaking with various intonations according to their respective cultural habits; the students shared information about the culture in their area; they appeared to respect and to appreciate each other when giving ideas to each other. This research concluded that online learning through PERMATA program was effective in increasing the cultural literacy of PGSD students.